Preparation, characterization and antibacterial properties of ZnO/kaoline nanocomposites - Dědková, Kateřina; Janíková, Barbora; Matějová, Kateřina; Peikertová, Pavlína; Neuwirthová, Lucie; Holešinský, Jan; Kukutschová, Jana (Journal of photochemistry and photobiology. B, Biology, 2015)
This paper describes laboratory preparation, characterization and antibacterial activity testing of ZnO/kaoline composites. ZnO/kaoline composites with 50 wt.% of ZnO were laboratory prepared, dried at 105 °C and calcined at 500 °C. XRPD analysis revealed that thermal treatment caused the phase transformation of Zn containing precursor into ZnO. Scanning and transmission electron microscopy techniques were used for characterization of morphology of the prepared samples. A standard microdilution test was used for evaluation of antibacterial activity using four common human pathogens (Staphylococcus aureus, Escherichia coli, Enterococcus faecalis and Pseudomonas aeruginosa). Daylight was used for induction photocatalytically based antibacterial activity. Second possible explanation of antibacterial activity of ZnO/kaoline could be the presence of biologically available forms of zinc. During the antibacterial activity assays the ZnO/kaoline composites exhibited antibacterial activity, where differences in an onset of the antibacterial activity and activity against bacterial strains were observed. The highest antibacterial activity was observed against S. aureus, where the lowest value of minimum inhibitory concentration was determined equal to 0.41 mg/ml.
Keywords: Enterococcus faecalis; kaolin; Kaolin; Nanocomposites; Staphylococcus aureus; Zinc Oxide; Light; Catalysis; nanokompozity; světlo; X-Ray Diffraction; antibakteriální látky; Anti-Bacterial Agents; difrakce rentgenového záření; Escherichia coli; oxid zinečnatý; Pseudomonas aeruginosa; katalýza